Employees' use, preferences, and restorative benefits of green outdoor environments at hospitals - Abdul Shukor, Shureen Faris; Stigsdotter, Ulrika Karlsson; Lottrupb, Lene; Nilsson, Kjell Svenne Bernhard (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
Work-related stress is an increasing problem among healthcare workers all over the world. The overall hypothesis of this study is that green outdoor environments (GOE) at hospitals may contribute to a less stressful working environment by offering psychological restoration. This study investigates GOE at five acute-care hospitals located in the capital region of Denmark. It aims to identify how the GOE are used by the employees and their potential for restoration. Data was collected through a survey where 183 employees completed an on-site questionnaire which included the perceived restorativeness scale (PRS). The main results indicate that the GOE are mostly used for a short while by the employees; the main activity is to have lunch, but they are also used actively to get away from the stressful working environment. The results from this study contribute to the international research on GOE at hospitals, and may be of inspiration for designers as well as for hospital staff and administrators.